Fbxo45 Binds SPRY Motifs in the Extracellular Domain of N-Cadherin and Regulates Neuron Migration during Brain Development - Na, Youn (Mol Cell Biol, 2020)
Several events during the normal development of the mammalian neocortex depend on N-cadherin, including the radial migration of immature projection neurons into the cortical plate. Remarkably, radial migration requires the N-cadherin extracellular domain but not N-cadherin-dependent homophilic cell-cell adhesion, suggesting that other N-cadherin-binding proteins may be involved. We used proximity ligation and affinity purification proteomics to identify N-cadherin-binding proteins. Both screens detected MycBP2 and SPRY domain protein Fbxo45, two components of an intracellular E3 ubiquitin ligase. Fbxo45 appears to be secreted by a nonclassical mechanism, not involving a signal peptide and not requiring transport from the endoplasmic reticulum to the Golgi apparatus. Fbxo45 binding requires N-cadherin SPRY motifs that are not involved in cell-cell adhesion. SPRY mutant N-cadherin does not support radial migration in vivo. Radial migration was similarly inhibited when Fbxo45 expression was suppressed. The results suggest that projection neuron migration requires both Fbxo45 and the binding of Fbxo45 or another protein to SPRY motifs in the extracellular domain of N-cadherin.